Diversity and Functional Analysis of the FeMo-Cofactor Maturase NifB - Arragain, Simon; Jiménez-Vicente, Emilio; Scandurra, Alessandro A.; Burén, Stefan; Rubio, Luis M.; Echavarri-Erasun, Carlos (Frontiers in Plant Science, 2017)
One of the main hurdles to engineer nitrogenase in a non-diazotrophic host is achieving NifB activity. NifB is an extremely unstable and oxygen sensitive protein that catalyzes a low-potential SAM-radical dependent reaction. The product of NifB activity is called NifB-co, a complex [8Fe-9S-C] cluster that serves as obligate intermediate in the biosyntheses of the active-site cofactors of all known nitrogenases. Here we study the diversity and phylogeny of naturally occurring NifB proteins, their protein architecture and the functions of the distinct NifB domains in order to understand what defines a catalytically active NifB. Focus is on NifB from the thermophile Chlorobium tepidum (two-domain architecture), the hyperthermophile Methanocaldococcus infernus (single-domain architecture) and the mesophile Klebsiella oxytoca (two-domain architecture), showing in silico characterization of their nitrogen fixation (nif) gene clusters, conserved NifB motifs, and functionality. C. tepidum and M. infernus NifB were able to complement an Azotobacter vinelandii (ΔnifB) mutant restoring the Nif+ phenotype and thus demonstrating their functionality in vivo. In addition, purified C. tepidum NifB exhibited activity in the in vitro NifB-dependent nitrogenase reconstitution assay. Intriguingly, changing the two-domain K. oxytoca NifB to single-domain by removal of the C-terminal NifX-like extension resulted in higher in vivo nitrogenase activity, demonstrating that this domain is not required for nitrogen fixation in mesophiles.